Local Level Participatory Budgeting: Case of Banyuwangi Regency, Indonesia - Septalinda, Ficky; Supranoto, Supranoto; Supriyono, Bambang; Suryawati, Dina (Iapa Proceedings Conference, 2024)
The purpose of this study is to examine the implementation process of public budgeting through a recess forum in Banyuwangi Regency. One of the most radical changes in the development planning process in Indonesia is the emergence of a bottom-up planning model, which was marked by the issuance of Law No.22/2009 on Regional Autonomy. One of the best practices that is considered very successful in bottom-up planning forums is participatory budgeting in Brazil, which was later adopted by many countries around the world. In Indonesia, Development Planning Deliberation is one of the forums considered to represent participatory budgeting, but a number of shortcomings in the implementation of Development Planning Deliberation have caused the community to look for other forums to convey various development proposals in the region. One forum that is considered more effective is through recess forums conducted by legislative institutions. This research was conducted to examine in depth the process and dynamics of participatory budgeting and the participatory budgeting model in the recess forum in Banyuwangi Regency. The method used in this research is qualitative with a Naturalist methodology approach Based on the research conducted, the public budgeting process through the recess forum cannot be implemented as dimensions in participatory budgeting. This is because the public budgeting process through the recess forum will always be tied to the political dynamics being faced by Local house of representatives member. Meanwhile, the political dynamics that occur are determined by political interactions between political actors, especially to gain political support in general elections.